1)sen(x + π) = sen(x).cos(π) + sen(π).cos(x)

MMN e Propedêutica: 1)sen(x + π) = sen(x).cos(π) + sen(π).cos(x):


1)sen(x + π) = sen(x).cos(π) + sen(π).cos(x)

Trigonometria

1)sen(x + π) = sen(x).cos(π) + sen(π).cos(x)

Como π rad = 180º Temos que:

sen π = 0

cos π = -1

Assim

sen(x + π) = sen(x).(-1)) + 0.cos(x)

sen(x + π) = - sen(x)

sen(x + π) = sen(x).cos(π) + sen(π).cos(x)

Como π rad = 180º Temos que:

sen π = 0

cos π = -1

Assim

sen(x + π) = sen(x).(-1)) + 0.cos(x)

sen(x + π) = - sen(x)

1)sen(x + π) = sen(x).cos(π) + sen(π).cos(x)

Como π rad = 180º Temos que:

sen π = 0

cos π = -1

Assim

sen(x + π) = sen(x).(-1)) + 0.cos(x)

sen(x + π) = - sen(x)

2)sen(x + 2π) = sen(x).cos(2π) + sen(2π).cos(x)

Como π rad = 360º Temos que:

sen 2π = 0

cos π = 1

Assim

sen(x + 2π) = sen(x).(1) + 0.cos(x)

sen(x + 2π) = sen(x)

QSL?